Simulation in the field of transfusion medicine: Scope and utility - Abhishekh Basavarajegowda; Dinker R Pai; Y. C. Nalini (Asian Journal of Transfusion Science)
Simulation in medical education has made significant inroads in most of the specialties in some form or the other. Transfusion medicine, as a branch, being a new specialty, is imbibing a few things from the world of simulation and provides immense scope for its utilization, given its broad applicability as well as necessity. In the current Indian scenario of transfusion medicine, wherein the transfusion process has undergone significant changes involving critical steps, with fewer but can be serious complications arising due to the transfusion process, it is desirable for students and the staff involved to practice on the simulators to attain the desired level of competency as it allows the practice of hands-on invasive procedures before performing the actual process. The principles, pedagogies, and educational strategies with their modalities used in health care simulation like case-based scenarios, physical models, computer systems, standardized patients, mannequins, virtual reality, and integrated simulators are all being used and the scope for improvisation is always in the fore with technical advancements. The transfusion and related activities include significant risks, so regular training is essential. The costs are also reasonably high, and focusing on being time-efficient is essential as many scenarios need immediate attention and management. Simulation in transfusion medicine has farsighted returns wherein there is the possibility of defining goals and objectives and ensuring that they could be adjusted to the individual learners as per their knowledge and skill level. The simulations can be set up that can train as well as assess cognitive, affective, and psychomotor domains simultaneously in transfusion using multiple modalities.